Preparation method and application of copper-iron sulfide nitrogen-doped porous carbon composite material
The preparation of copper-iron sulfide nitrogen-doped porous carbon composite material by mechanical ball milling has solved the shortcomings of the existing sodium ion battery anode materials in high sodium storage capacity and cycle stability, and achieved simple operation, green and environmentally friendly low-cost preparation, and the material exhibits excellent rate performance and cycle life.
Patent Information
- Application Number
- CN202411681782.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing sodium ion battery anode materials have shortcomings in high sodium storage capacity and cycle stability, and traditional preparation methods require high temperature and high pressure, which increases energy consumption and cost, and poses safety hazards.
Copper-iron Prussian blue precursors were prepared by mechanical ball milling, and the copper-iron sulfide nitrogen-doped porous carbon composite material was obtained after high-temperature pyrolysis and vapor phase vulcanization. This method is simple to operate, green and environmentally friendly, and does not require organic solvents and high temperature and high pressure environments.
The prepared copper-iron sulfide nitrogen-doped porous carbon composite material exhibits excellent rate performance and long cycle life. It is suitable for sodium ion battery negative electrode materials, and is low-cost and suitable for industrial production.
Smart Images

Figure CN119750657A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for sodium ion batteries, and more specifically relates to a preparation method and application of a copper-iron sulfide nitrogen-doped porous carbon composite material. Background Art
[0002] As the pace of global energy transformation accelerates, limited lithium resource reserves restrict the large-scale energy storage application of lithium-ion batteries (LIBs) in the future. Therefore, it is crucial to explore supplementary alternatives to LIBs. Among them, sodium-ion batteries (SIBs) have attracted widespread attention because of their similar working mechanism to lithium-ion batteries, low cost and abundant resources. However, due to the large radius of Na+, the traditional negative electrode material graphite cannot meet the requirements of high sodium storage capacity. The original research based on LIBs negative electrode materials is not suitable for SIBs. Therefore, exploring and developing new negative electrode materials that match the positive electrode materials and have excellent performance has important research and application value. At present, electrode materials are developing towards the compatibility of high reversible specific capacity and high cycle stability, thereby improving the energy density, cycle life and fast charging performance of SIBs.
[0003] Transition metal sulfides have become one of the hot topics in the research of negative electrode materials for SIBs due to their excellent theoretical specific capacity and abundant active sites. Compared with single metal sulfides, bimetallic sulfides can produce synergistic effects between heterojunctions, and at the same time have lower energy band gaps and higher electron / ion conductivity, which has attracted widespread attention in the field of energy storage. However, due to the sodium storage and release reaction mechanisms such as continuous conversion / alloying in sodium-ion batteries, the volume changes of transition metal sulfide electrode materials are more significant. To solve the above problems, constructing a heterojunction based on bimetallic sulfides can not only effectively improve the structure and electrochemical stability of transition metal sulfides, but also help to accelerate the transmission of electrons / ions in electrode materials.
[0004] But so far, in the traditional preparation method, such as Chinese patent CN110289416A, a bismuth molybdenum oxide precursor is prepared by a solvent thermal method, and then Mo7S8 / Bi2S3 nanomaterials are obtained by annealing. The bismuth molybdenum bimetallic sulfide prepared by the patent is made into a sodium ion battery electrode, showing high cycle stability and excellent long cycle performance, but its synthesis conditions are usually harsh, requiring high temperature, high pressure and long reaction conditions, which not only increases the energy consumption and cost of material preparation, but also has certain safety hazards, limiting its practical application. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing a copper iron sulfide nitrogen-doped porous carbon composite material and its application in view of the above problems. A copper iron Prussian blue precursor is prepared by a mechanical ball milling process, and a copper iron sulfide / nitrogen-doped porous carbon composite material is obtained by high-temperature pyrolysis and gas phase sulfidation. The method has the advantages of simple operation, green environmental protection, and high yield. The copper iron sulfide nitrogen-doped porous carbon composite material finally obtained can be used as a sodium ion negative electrode material with excellent rate performance and long cycle life.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] One of the technical solutions of the present invention: a method for preparing a copper-iron sulfide nitrogen-doped porous carbon composite material, comprising the following steps:
[0008] (1) copper salt, potassium ferrocyanide, nitrogen source and polyethylene glycol are mixed and ball-milled to obtain a copper-iron Prussian blue precursor;
[0009] (2) pyrolyzing the copper-iron Prussian blue precursor under an inert atmosphere, washing to remove impurities, and drying to obtain an intermediate product;
[0010] (3) The intermediate product and a sulfur source are heat treated under an inert atmosphere to obtain a copper iron sulfide / nitrogen-doped porous carbon composite material.
[0011] In the above-mentioned preparation method of the present invention, the reaction principle is as follows: the energy and mechanical force generated during the ball milling process induce the metal copper ions to react with the ferricyanide to form a copper-iron Prussian blue precursor. Subsequently, the precursor obtained by ball milling is heat-treated under the protection of an inert atmosphere, and the organic components are pyrolyzed at high temperature to form a nitrogen-doped carbon framework, and polyethylene glycol can not only be used as a carbon source, but also as a template to induce the material to grow into a two-dimensional sheet structure, promote the formation of a porous structure, and decompose to form a carbon framework. At the same time, a portion of the copper ions are carbon-thermally reduced to metallic copper, and a portion of the iron ions react with carbon to form an iron-carbon compound to obtain a black powder copper / iron-carbon compound / nitrogen-doped carbon composite material with a mixed phase. Finally, a gas phase sulfurization treatment is performed, and the sulfur source sublimates at high temperature to become sulfur vapor, and the metal copper and the iron-carbon compound react to form copper sulfide / iron disulfide, and the excess sulfur is removed in the form of gas to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0012] In order to solve the problems of poor conductivity, large volume change and slow ion diffusion kinetics of transition metal sulfides during operation. The present invention uses a simple and efficient mechanical ball milling method to provide a copper iron sulfide nitrogen-doped porous carbon composite material. A heterojunction is formed between CuS / FeS2 in the designed composite structure material, and a built-in electric field is easily formed between the heterostructures, which can greatly accelerate the transmission of electrons and ions, improve the adsorption of sodium ions, and thus improve the rate performance of battery materials; the surface and interior of the material form a porous structure, and the presence of the CuS / FeS2 heterojunction forms more defects, thereby increasing the active sites of the bulk and surface, so that the composite material has higher electrochemical activity. The internal and external porous structures are conducive to eliminating the volume effect of the electrode material, and N doping increases the adsorption sites for sodium ion batteries and improves the conductivity, thereby effectively improving the sodium storage performance of the electrode material. The raw materials prepared by the present invention are cheap, widely available, simple in operation process, high in yield, and the material has excellent charge and discharge performance, which is convenient for industrial production.
[0013] Preferably, the copper salt is any one of copper chloride, copper acetate and copper nitrate; and the nitrogen source is any one of melamine, nitrilotriacetic acid and glycine.
[0014] Preferably, in step (1), the mass ratio of the copper salt, potassium ferrocyanide and nitrogen source is (1-5):(1-3):1.
[0015] Preferably, in step (1), the mass ratio of the total mass of the copper salt, potassium ferrocyanide and the nitrogen source to the mass ratio of the polyethylene glycol is (1-4):1.
[0016] Preferably, in step (1), the mass ratio of the total mass of the copper salt, potassium ferrocyanide, nitrogen source and polyethylene glycol to the mass ratio of the ball milling beads is 1:(5-40).
[0017] Preferably, in step (1), the ball milling time is 1 to 12 hours and the rotation speed is 200 to 600 rpm.
[0018] Preferably, in step (2), the pyrolysis temperature is 400-1000°C, and the heating rate is 2-10°C·min -1 , the insulation time is 1 to 5 hours; the inert atmosphere is nitrogen or argon.
[0019] Preferably, in step (3), the mass ratio of the intermediate product to the sulfur source is 1:(3-5); and the sulfur source is any one of sulfur powder, thiourea and thioacetamide.
[0020] Preferably, in step (3), the heat treatment temperature is 300-600° C., and the holding time is 1-3 hours; and the inert atmosphere is nitrogen or argon.
[0021] The second technical solution of the present invention: an application of the copper-iron sulfide nitrogen-doped porous carbon composite material obtained by the above preparation method as a negative electrode material for a sodium ion battery.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The present invention adopts a mechanochemical method to prepare a copper-iron Prussian blue precursor, and provides a method for preparing a copper-iron sulfide nitrogen-doped porous carbon composite material. Unlike the traditional solvothermal method, it does not require an organic solvent and a high-temperature and high-pressure reaction environment. The preparation method is simple and easy to operate, safe and pollution-free, low-cost, and can be prepared on a large scale.
[0024] (2) The copper-iron sulfide nitrogen-doped porous carbon composite material prepared by the present invention has the synergistic effect of bimetallic sulfide and nitrogen-doped porous carbon composite. The carbon matrix obtained by polyethylene glycol carbonization is embedded with metal nanoparticles, which improves the electronic conductivity of the electrode material. Nitrogen doping expands the carbon interlayer spacing, making it easier for sodium ions with larger ionic radius to embed and de-embed in the interlayer spacing, while providing abundant active sites to enhance ion storage.
[0025] (3) The copper iron sulfide nitrogen-doped porous carbon composite material prepared by the present invention has a porous structure, which is not only conducive to full contact with the electrolyte, but also can shorten the transmission distance of electrons / ions, accelerate the reaction kinetics, effectively adapt to the volume expansion during the insertion / deinsertion of sodium ions, and has outstanding rate performance and stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the X-ray diffraction pattern of the final product prepared in Example 3;
[0027] Figure 2 is a scanning electron microscope image of the final product prepared in Example 2;
[0028] Figure 3 This is a scanning electron microscope image of the final product prepared in Comparative Example 1;
[0029] Figure 4 The battery rate performance diagram of the final products prepared in Comparative Example 1 and Example 2. DETAILED DESCRIPTION
[0030] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0031] Example 1
[0032] (1) 0.4 g of copper acetate, 0.3 g of potassium ferrocyanide, 0.1 g of glycine and 0.8 g of polyethylene glycol (average molecular weight 4200-4800 g / mol, the same below) were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milling was performed for a total of 8 hours at a rotation speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0033] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 800°C at a heating rate and then pyrolyzed for 3 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0034] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 500°C for 2 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0035] Example 2
[0036] (1) 0.4 g of copper nitrate, 0.3 g of potassium ferrocyanide, 0.1 g of melamine and 0.5 g of polyethylene glycol were added to an agate ball mill in sequence; 20 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 6 hours at a speed of 500 rpm to obtain a copper-iron Prussian blue precursor;
[0037] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 5 °C min -1 The temperature was raised to 700°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0038] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:5, and heat treated at 300°C for 2 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0039] Example 3
[0040] (1) 0.6 g of copper acetate, 0.4 g of potassium ferrocyanide, 0.2 g of melamine and 0.6 g of polyethylene glycol were added to an agate ball mill in sequence; 30 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milling was performed for a total of 6 hours at a rotation speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0041] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min-1 The temperature was raised to 800°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0042] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 2 h in a nitrogen atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0043] Example 4
[0044] (1) 0.5 g of copper chloride, 0.6 g of potassium ferrocyanide, 0.2 g of glycine and 0.8 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 3 h at a speed of 500 rpm to obtain a copper-iron Prussian blue precursor; (2) the copper-iron Prussian blue precursor was subjected to high-temperature pyrolysis under argon atmosphere protection and heated at 2 °C min -1 The temperature was raised to 500°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0045] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:4, and heat treated at 500°C for 2 h in a nitrogen atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0046] Example 5
[0047] (1) 0.5 g of copper acetate, 0.7 g of potassium ferrocyanide, 0.5 g of glycine and 1 g of polyethylene glycol were added to an agate ball mill in sequence; 20 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milling was performed for a total of 5 h at a speed of 500 rpm to obtain a copper-iron Prussian blue precursor; (2) the copper-iron Prussian blue precursor was subjected to high-temperature pyrolysis under argon atmosphere protection and heated at 2 °C min -1 The temperature was raised to 500°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0048] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 600°C for 3 h in a nitrogen atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0049] Example 6
[0050] (1) 0.6 g of copper chloride, 0.5 g of potassium ferrocyanide, 0.2 g of melamine and 0.5 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 4 hours at a speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0051] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 600°C at a heating rate and then pyrolyzed for 3 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0052] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 1 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0053] Example 7
[0054] (1) 0.6 g of copper chloride, 0.8 g of potassium ferrocyanide, 0.5 g of glycine and 0.7 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 7 hours at a speed of 500 rpm to obtain a copper-iron Prussian blue precursor; (2) the copper-iron Prussian blue precursor was subjected to high-temperature pyrolysis under argon atmosphere protection and heated at 3 °C min -1 The temperature was raised to 500°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0055] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:4, and heat treated at 350°C for 2 h in a nitrogen atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0056] Comparative Example 1 (Compared with Example 2, melamine and polyethylene glycol were not added)
[0057] (1) 0.4 g of copper nitrate and 0.3 g of potassium ferrocyanide were added to an agate ball mill in sequence; 20 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 6 hours at a speed of 500 rpm to obtain a copper-iron Prussian blue precursor;
[0058] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 5 °C min -1The temperature was raised to 700°C at a heating rate and then pyrolyzed for 2 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0059] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:5, and heat treated at 300°C for 2 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0060] Comparative Example 2 (Compared with Example 6, no polyethylene glycol was added)
[0061] (1) 0.6 g of copper chloride, 0.5 g of potassium ferrocyanide, and 0.2 g of melamine were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 4 hours at a speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0062] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 600°C at a heating rate and then pyrolyzed for 3 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0063] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 1 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0064] Comparative Example 3 (Compared with Example 4, no melamine was added)
[0065] (1) 0.6 g of copper chloride, 0.5 g of potassium ferrocyanide and 0.5 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 4 hours at a speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0066] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 600°C at a heating rate and then pyrolyzed for 3 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0067] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 1 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0068] Comparative Example 4 (excessive addition of polyethylene glycol compared to Example 6)
[0069] (1) 0.6 g of copper chloride, 0.5 g of potassium ferrocyanide, 0.2 g of melamine and 1.5 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 4 hours at a speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0070] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 600°C at a heating rate and then pyrolyzed for 3 hours to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0071] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 1 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0072] Comparative Example 5 (Compared with Example 6, the pyrolysis temperature is too low and the pyrolysis time is too short)
[0073] (1) 0.6 g of copper chloride, 0.5 g of potassium ferrocyanide, 0.2 g of melamine and 0.5 g of polyethylene glycol were added to an agate ball mill in sequence; 40 g of agate ball mill beads were added to the agate ball mill; the ball mill was transferred to a planetary ball mill and assembled, and then ball milled for a total of 4 hours at a speed of 400 rpm to obtain a copper-iron Prussian blue precursor;
[0074] (2) The copper-iron Prussian blue precursor was pyrolyzed under argon atmosphere at 3 °C min -1 The temperature was raised to 300°C at a heating rate and then pyrolyzed for 1 hour to obtain a pyrolysis product; the pyrolysis product was soaked in deionized water for 1 hour, and the intermediate product was collected by centrifugation;
[0075] (3) The intermediate product was mixed with sulfur powder in a mass ratio of 1:3, and heat treated at 400°C for 1 h in an argon atmosphere to obtain a copper-iron sulfide nitrogen-doped porous carbon composite material.
[0076] Performance Testing
[0077] The composite materials obtained in Examples 1 to 7 and Comparative Examples 1 to 5 were ground and stirred with the conductive agent SuperP and the binder polyvinylidene fluoride in a ratio of 7:2:1 until they were evenly mixed, coated on a copper foil, and then punched into discs with a diameter of 12 mm as the negative electrode, metallic sodium as the counter electrode, 1M sodium hexafluorophosphate (NaPF6) dissolved in dimethyl ether as the electrolyte, and glass fiber as the diaphragm. They were assembled into CR2025 button batteries in a glove box filled with argon atmosphere and with a water oxygen value of less than 0.01ppm. After being left for 24 hours, constant current charge and discharge tests were carried out in the range of 0.01 to 3V using a Xinwei tester.
[0078] Table 1 Capacity retention rate after 200 cycles of Examples 1 to 7 and Comparative Examples 1 to 4
[0079] Case Capacity retention after 200 cycles Example 1 78.3% Example 2 87.1% Example 3 82.3% Example 4 77.4% Example 5 79.5% Example 6 85.9% Example 7 79.3% Comparative Example 1 69.8% Comparative Example 2 73.5% Comparative Example 3 74.7% Comparative Example 4 76.2% Comparative Example 5 79.3%
[0080] As shown in Table 1, in combination with Examples 1 to 7 and Comparative Examples 1 to 5, it can be seen that the capacity retention rate of Comparative Examples 2-5 is lower than that of Example 6. This is due to the synergistic effect of the bimetallic sulfide and nitrogen-doped porous carbon composite in the present invention, which effectively adapts to the volume expansion during the insertion / deinsertion of sodium ions, and provides abundant active sites to enhance the storage of ions, with outstanding rate performance and stable cycle performance. However, the ratio of nitrogen source and polyethylene glycol is too high, which affects the exposure and conductivity of active sites; the pyrolysis temperature is low, the carbonization is incomplete, resulting in poor conductivity and structural stability of the material; the ball milling time is short and the ball-to-material ratio is insufficient, resulting in insufficient mixing of the precursor; therefore, the performance of the composite material can be fully improved by reasonably controlling the ball milling parameters, the ratio of nitrogen source and polyethylene glycol, and the pyrolysis temperature, while significantly improving the structural cycle stability of the composite material and extending its cycle life.
[0081] like Figure 1 Shown is the X-ray diffraction spectrum of Example 3. It can be seen from the figure that the diffraction peaks of CuS and FeS2 are in good agreement with the standard cards, the peaks are strong and sharp, and the broad diffraction peak appearing near 26° belongs to amorphous carbon, indicating that the CuS / FeS2 and carbon nanocomposite material has been successfully prepared.
[0082] like Figure 2 The figure shows a scanning electron microscope image of the composite material in Example 2. It can be seen from the figure that the material is a corrugated lamellar porous structure, and the nanoparticles CuS / FeS2 are uniformly grown on the surface and inside of the porous carbon matrix. The porous structure of the carbon matrix originates from the decomposition of organic components during high-temperature pyrolysis, which is not only conducive to the contact between the electrode / electrolyte, but also plays a key role in adapting to the volume expansion of the electrode material and ensuring rapid electron / ion transmission.
[0083] like Figure 3 The SEM image of the composite material in Comparative Example 1 is shown. Figure 2 The morphology is quite different, it is composed of many particles agglomerated and of uneven size.
[0084] like Figure 4 The figure shows the battery rate performance of the final product prepared in Example 2. The sodium ion battery is at 0.2, 0.5, 1, 2, 5 and recovers 0.2 A·g -1 The reversible specific capacities at different current densities are 732, 725, 713, 669, 602, and 781 mAh·g, respectively. -1 , showing excellent rate performance.
[0085] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a copper-iron sulfide nitrogen-doped porous carbon composite material, characterized in that: The steps include: (1) copper salt, potassium ferrocyanide, nitrogen source and polyethylene glycol are mixed and ball-milled to obtain a copper-iron Prussian blue precursor; (2) pyrolyzing the copper-iron Prussian blue precursor under an inert atmosphere, washing to remove impurities, and drying to obtain an intermediate product; (3) The intermediate product and a sulfur source are heat treated in an inert atmosphere to obtain a copper iron sulfide / nitrogen-doped porous carbon composite material.
2. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1, characterized in that: The copper salt is any one of copper chloride, copper acetate and copper nitrate; the nitrogen source is any one of melamine, nitrilotriacetic acid and glycine.
3. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1, characterized in that: In step (1), the mass ratio of the copper salt, potassium ferrocyanide and nitrogen source is (1-5): (1-3):
1.
4. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1, characterized in that: In step (1), the total mass ratio of the copper salt, potassium ferrocyanide and nitrogen source to the polyethylene glycol is (1-4):
1.
5. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1, characterized in that: In step (1), the mass ratio of the total mass of the copper salt, potassium ferrocyanide, nitrogen source and polyethylene glycol to the mass ratio of the ball milling beads is 1:(5-40).
6. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to any one of claims 1 to 5, characterized in that: In step (1), the ball milling time is 1 to 12 hours and the rotation speed is 200 to 600 rpm.
7. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to any one of claims 1 to 5, characterized in that: In step (2), the pyrolysis temperature is 400-1000°C, and the heating rate is 2-10°C·min -1 , the insulation time is 1 to 5 hours; the inert atmosphere is nitrogen or argon.
8. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1, characterized in that: In step (3), the mass ratio of the intermediate product to the sulfur source is 1:(3-5); the sulfur source is any one of sulfur powder, thiourea and thioacetamide.
9. The method for preparing the copper-iron sulfide nitrogen-doped porous carbon composite material according to claim 1 or 8, characterized in that: In step (3), the heat treatment temperature is 300-600° C., and the insulation time is 1-3 hours; and the inert atmosphere is nitrogen or argon.
10. Use of the copper-iron sulfide nitrogen-doped porous carbon composite material obtained by the preparation method according to any one of claims 1 to 9 as a negative electrode material for a sodium ion battery.
Citation Information
Patent Citations
Preparation method of negative electrode material bismuth-molybdenum bimetallic sulfide of sodium ion battery
CN110289416A
Controllable synthesis method of N-doped graphitized carbon ball with hollow structures
CN103183341A
Metal sulfide / nitrogen-doped carbon electrocatalyst derived from Prussian blue analogue as well as preparation method and application of metal sulfide / nitrogen-doped carbon electrocatalyst
CN113388847A
Cubic cage-shaped ferrous disulfide-manganese sulfide composite nitrogen-doped carbon skeleton nanometer material, preparation method and application in sodium ion battery
CN117476903A
Method for preparing nickel-iron sulfide porous carbon composite material based on mechanochemical method and application of nickel-iron sulfide porous carbon composite material
CN118099415A